Bark beetle mycobiome: collaboratively defined research priorities on a widespread insect-fungus symbiosis - Jiri Hulcr; Irene Barnes; Z. Wilhelm De Beer; Tuan A. Duong; Romina Gazis; Andrew J. Johnson; Michelle A. Jusino; Matthew T. Kasson; You Li; Shannon Lynch; Chase Mayers; Tendai Musvuugwa; et al. (Symbiosis, 2020)
One of the main threats to forests in the Anthropocene are novel or altered interactions among trees, insects and fungi. To critically assess the contemporary research on bark beetles, their associated fungi, and their relationships with trees, the international Bark Beetle Mycobiome research coordination network has been formed. The network comprises 22 researchers from 17 institutions. This forward-looking review summarizes the group’s assessment of the current status of the bark beetle mycobiome research field and priorities for its advancement. Priorities include data mobility and standards, the adoption of new technologies for the study of these symbioses, reconciliation of conflicting paradigms, and practices for robust inference of symbiosis and tree epidemiology. The Net work proposes contemporary communication strategies to interact with the global community of researchers studying symbioses and natural resource managers. We conclude with a call to the broader scientific community to participate in the network and contribute their perspectives.

Know your farmer: Ancient origins and multiple independent domestications of ambrosia beetle fungal cultivars - Dan Vanderpool; Ryan R. Bracewell; John P. McCutcheon (Molecular Ecology, 2018)
Bark and ambrosia beetles are highly specialized weevils (Curculionidae) that have established diverse symbioses with fungi, most often from the order Ophiostomatales (Ascomycota, Sordariomycetes). The two types of beetles are distinguished by their feeding habits and intimacy of interactions with their symbiotic fungi. The tree tissue diet of bark beetles is facilitated by fungi, while ambrosia beetles feed solely on fungi that they farm. The farming life history strategy requires domestication of a fungus, which the beetles consume as their sole food source. Ambrosia beetles in the subfamily Platypodinae originated in the mid‐Cretaceous (119–88 Ma) and are the oldest known group of farming insects. However, attempts to resolve phylogenetic relationships and the timing of domestication events for fungal cultivars have been largely inconclusive. We sequenced the genomes of 12 ambrosia beetle fungal cultivars and bark beetle associates, including the devastating laurel wilt pathogen, Raffaelea lauricola , to estimate a robust phylogeny of the Ophiostomatales. We find evidence for contemporaneous diversification of the beetles and their associated fungi, followed by three independent domestication events of the ambrosia fungi genus Raffaelea . We estimate the first domestication of an Ophiostomatales fungus occurred ~86 Ma, 25 million years earlier than prior estimates and in close agreement with the estimated age of farming in the Platypodinae (96 Ma). Comparisons of the timing of fungal domestication events with the timing of beetle radiations support the hypothesis that the first large beetle radiations may have spread domesticated “ambrosia” fungi to other fungi‐associated beetle groups, perhaps facilitating the evolution of new farming lineages.

Unlocking the vault: next‐generation museum population genomics - Ke Bi; Tyler Linderoth; Dan Vanderpool; Jeffrey M. Good; Rasmus Nielsen; Craig Moritz (Molecular Ecology, 2013)
Natural history museum collections provide unique resources for understanding how species respond to environmental change, including the abrupt, anthropogenic climate change of the past century. Ideally, researchers would conduct genome‐scale screening of museum specimens to explore the evolutionary consequences of environmental changes, but to date such analyses have been severely limited by the numerous challenges of working with the highly degraded DNA typical of historic samples. Here, we circumvent these challenges by using custom, multiplexed, exon capture to enrich and sequence ~11 000 exons (~4 Mb) from early 20th‐century museum skins. We used this approach to test for changes in genomic diversity accompanying a climate‐related range retraction in the alpine chipmunks ( T amias alpinus ) in the high Sierra Nevada area of California, USA . We developed robust bioinformatic pipelines that rigorously detect and filter out base misincorporations in DNA derived from skins, most of which likely resulted from postmortem damage. Furthermore, to accommodate genotyping uncertainties associated with low‐medium coverage data, we applied a recently developed probabilistic method to call single‐nucleotide polymorphisms and estimate allele frequencies and the joint site frequency spectrum. Our results show increased genetic subdivision following range retraction, but no change in overall genetic diversity at either nonsynonymous or synonymous sites. This case study showcases the advantages of integrating emerging genomic and statistical tools in museum collection‐based population genomic applications. Such technical advances greatly enhance the value of museum collections, even where a pre‐existing reference is lacking and points to a broad range of potential applications in evolutionary and conservation biology.